Clonal hematopoiesis of indeterminate potential and heart failure - E. A. Lyasnikova; L. Yu Ivanchenko; S. N. Kozlova; M. Yu. SITNIKOVA; A. A. Kostareva; E. V. Shlyakhto (Российский кардиологический журнал)
Modern studies demonstrate that clonal hematopoiesis of indeterminate potential (CHIP) is a risk factor for the development and prognosis of heart failure (HF) of various origin. The pathophysiology and consequences of CHIP are gene-specific. The mechanisms involved in this process are complex and indicate the central role of systemic and myocardial inflammation, including the immune response dependent on the inflammasome/interleukin-1β/interleukin-6 cascade. CHIP and associated inflammatory pathways represent a powerful potential target, which rationales the research in the area of various HF stages and markers of this genetic phenomenon. A better understanding of the interactions between mutant clones, immune pathways, chronic inflammation and clinical implementation in HF may be important in the context of precision and personalized medicine.